2014
DOI: 10.3399/bjgp14x677167
|View full text |Cite
|
Sign up to set email alerts
|

Detection of heart disease by open access echocardiography: a retrospective analysis of general practice referrals

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…Although routine screening is likely to be difficult to be implemented widely in general practice as many GPs are under pressure with workload, it is more likely to be successful in targeted screening of patients at increased risk of cardiac disease. This was demonstrated in the audit of 2343 TTEs performed in the GP setting by the open access scheme reported by Chambers and coworkers ( 8 ). The most common indications for TTE in the GP setting in this study were murmur, suspected heart failure (only with elevated B-type natriuretic peptide), abnormal ECG, hypertension and cardiomegaly.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although routine screening is likely to be difficult to be implemented widely in general practice as many GPs are under pressure with workload, it is more likely to be successful in targeted screening of patients at increased risk of cardiac disease. This was demonstrated in the audit of 2343 TTEs performed in the GP setting by the open access scheme reported by Chambers and coworkers ( 8 ). The most common indications for TTE in the GP setting in this study were murmur, suspected heart failure (only with elevated B-type natriuretic peptide), abnormal ECG, hypertension and cardiomegaly.…”
Section: Discussionmentioning
confidence: 76%
“…Attempts to improve GP’s access to existing TTE services have also found a high rate of important cardiac pathology. The open-access echocardiography scheme allowed GP’s access to TTE laboratories at 133 hospitals in the UK ( 25 , 26 , 27 ) and generated an extra 2343 TTE studies over 2years, which identified significant cardiac pathology in 29% of patients ( 8 ). Gillespie and Pringle reported significant cardiac pathology in 29% of patients from a qualified TTE technician located in the general practice ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, auscultation is not commonly performed even for patients with symptoms45 and is insensitive. A survey of open access studies46 found that significant valve disease was suspected from a murmur in 127 patients but was unsuspected in a further 177 cases with a possible cardiac symptom, chronic obstructive pulmonary disease with disproportionate breathlessness or atrial fibrillation. Using these criteria and also age ≥75 years to focus point-of-care scans, moderate or severe valve disease was found in 2% in a GP practice 47…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of openaccess echocardiography varies between practices, by a factor of over 150 in one audit. 8 GPs recognise that interpretation of open-access reports is difficult, 9 meaning that, unless strong systems are in place, the diagnosis of valve disease may not be 'flagged' and an appropriate referral to specialist clinics may be missed.…”
Section: Barriers To Detection In the Communitymentioning
confidence: 99%